Photoelectrocatalytic reduction of co2 into methanol over cds modified copper based photocathode - Mostafa, Tarek (2020)
In the context of present technological advancement and relies on fossil fuel, the CO2 emission is inevitable, hence recycling the CO2 into fuel is appeared to be a most promising option to tackle the environmental and energy crisis. The CO2 conversion route includes the thermochemical, biological, electrocatalytic (EC), photocatalytic (PC) and photoelectrocatalytic (PEC) systems. The PC CO2 reduction utilizing the sunlight is considered to be the most promising ways, however, it suffers from low quantum efficiency due to the higher electron/hole (e-/h+) recombination rate. In this context, the PEC system which integrates the principles of PC and EC reduction of CO2 can effectively reduce the e-/h+ recombination as well as the externally applied potential endowing remarkable increase in quantum efficiency. In PEC CO2 reduction p-type photocathode is used and their catalytic activity and selectivity can be increased by creating heterojunction with n-type semiconductors that suppresses the e-/h+ recombination rate. In the present study, copper-based p-type semiconductor, such as copper oxide (CuO) and copper ferrite (CuFe2O4) was prepared by chemical precipitation and sol-gel method respectively and was further modified by cadmium sulfide (CdS) nanoparticles by ultrasound-assisted wet impregnation method. The synthesized catalysts were characterized by XRD, Raman spectroscopy, XPS, FESEM-EDX, TEM, BET, UVvisible and PL spectroscopy. The photo- and electrocatalytic activity were monitored by using linear sweep voltammetry (LSV) and chronoamperometry. Heterostructured CdS/ CuFe2O4 (~21 mA/cm2) photocathode showed ~2.5, ~2.9 and ~1.5 times higher reducing current compared to pure CuFe2O4 (~9 mA/cm2), CuO (~7 mA/cm2) and CdS/CuO (~12.22 mA/cm2) photocathode, respectively under CO2 and light on condition. The highest incident photon to current efficiency (IPCE) was obtained as ~12.1% for CdS/ CuFe2O4. IPCE specified that 10% CdS/CuFe2O4 has the ability to absorb the visible light that can lead the e-/h+generation and the charge transfer in this photocatalyst can drive the reduction of CO2. The photocurrent density followed the trend of CdS/ CuFe2O4>CdS/CuO>CuFe2O4>CuO. Products in aqueous phases were analyzed which confirmed the selective production of methanol with trace amounts of formaldehyde (HCHO) using CdS/CuFe2O4 photocathode. The highest methanol yield was found as 23.88 µmol. L -1cm-2 at an applied potential of -0.35V where the Quantum efficiency (QE) and Faradaic efficiency (FE) were 16.9 and 72% respectively. The charge transfer mechanism in the heterostructured photocathode was revealed which showed that the conduction band (CB) of the CdS could act as a CO2 reduction site by trapping photogenerated electrons from the highly photosensitive CuFe2O4 while the water oxidation could take place at the valance band (VB) of CuFe2O4. The present work demonstrates the facile fabrication of p-n heterostructured catalyst for the PEC reduction of CO2 with remarkable improvement in methanol yield under visible light illumination which can potentially be utilized as a platform to develop the photocathodes for PEC CO2 reduction systems.